Parallel algorithms for solving of multidimentional vibrational Shrodinger equation - Rakauskas, Rimantas-Jonas; Šulskus, Juozas; Vošterienė, Svajonė (Lietuvos matematikos rinkinys, 2002)
There is not abstract.